Intergenerational gaps and linguistic decline in Ecuador's indigenous communities: A socio-legal analysis - Ferruzola-Gómez, Enrique; Chávez-Morales, Claudia; Méndez-Carrillo, María del Carmen; Duchimaza-Supliguicha, Johanna (International Journal of Innovative Research and Scientific Studies, 2025)
This interdisciplinary study assesses the effectiveness of Ecuadorian legislation, specifically the Constitutions of 1998 and 2008, which are pioneers in the recognition of native peoples and nationalities, in protecting indigenous languages as fundamental cultural rights in the face of a marked linguistic decline. Using a mixed methodological approach, we examine the coherence between legislative intentions and their practical implementation in safeguarding indigenous linguistic diversity in Ecuador. Through a quantitative analysis based on data from the 2001, 2010, and 2022 population censuses, a significant reduction in the use of indigenous languages among the younger generations is evidenced, indicating a growth in the transmission gap. This finding highlights the urgent need to develop effective legislative and policy interventions that actively promote the use and transmission of these languages among future generations.